Formation of an Eﬀective System of Personnel Motivation at Industrial Enterprises of Ukraine (Laisvalaikio tyrimai, 2024)
It is found that the level of competitiveness of enterprises, and stability of functioning largely depends on the efficiency and results of the work of personnel, and the level of their skills. The quality and timeliness of tasks, production, and the formation of creative ideas depend on the qualifications of employees. Therefore, an important indicator of a company’s staff efficiency at the enterprise is labour productivity, the level which depends on the personnel policy, and the motivation system. It is determined that forms and methods of motivation affects the level of labour productivity, satisfaction with working conditions, interaction, and teamwork. It is determined that at industrial enterprises it is expedient to introduce modern forms of motivation of employees, which will affect not only the quality of staff work, increase interest in the results of work, but also the level of profitability, production, and sales volumes. Likewise, it  is proved that the introduction of various forms of stimulation of personnel in a complex will ensure the efficiency of work, and stability of the functioning of the enterpriset is found that the use forms and methods of motivation allows to establishment of the process of personnel management and ensures    the efficiency of their work. Among the problems of personnel motivation at enterprises are defined as limited amount of financial support, low level of wages, unfavourable      psychological climate in the team, limited access to information data, non-use of indirect methods of motivation, and inefficiency of personnel policy. Recommendations for improving the motivation of personnel at enterprises have been formed: conducting training and webinars for employees; advanced training and training in the field of software application; hiring qualified employees; study of the psychological climate in the team to  prevent problems and solve them; improvement of the system of formation of premiums; formation of a social package; promoting self-development and teamwork. It is proved that motivation affects labour  productivity, personnel management and the functioning of the firm , work results, and formation of competitive advantages. The system of personnel motivation for industrial enterprises has been improved, which consists of a set of elements and stages of formation, approbation, implementation, and improvement, which will contribute to increasing the effectiveness of employees, and the efficiency of enterprises.Keywords: motivation, personnel, productivity, industrial enterprises, efficiency, personnel management, personnel motivation system.